Acidity and Salinization of Soil Following the Application of Ashes from Biomass Combustion Under Different Crop Plant Species Cultivation - Małgorzata Szostek; Ewa Szpunar-Krok; Natalia Matłok; Anna Ilek; Klaudia Słowik; Maciej Kuboń (Applied Sciences)
Ashes from biomass combustion (BAs) are a valuable source of plant nutrients, making them suitable for fertilizing crops. BAs also contain components that directly affect soil environmental conditions, leading to improved growth and development of plants. Their deacidifying properties allow BAs to serve as a substitute for calcium fertilizers. However, they contain substantial amounts of components that can increase soil salinity, which can have negative effects. The aim of this study was to assess the impact of BAs on changes in pH and salinity of haplicluvisol soil under the cultivation of various plant species. The study also analyzed the effects of BAs on the content of total forms of calcium (Ca), magnesium (Mg), potassium (K), and sodium (Na) in the soil. The BAs used in the experiment were sourced from a combined heat and power plant that combusts forest and agricultural biomass. These BAs are distributed as a product for fertilizing agricultural land. However, their application is not subjected to further monitoring. The results indicated that the application of different doses of BAs significantly affected the pH of the analyzed soil. Compared to control objects, a significant increase in pH was observed, with these changes dependent on the species of the cultivated plant. Additionally, even the smallest doses of BAs caused an increase in the electrolytic conductivity (EC) of soil solutions, which serves as a measure of soil salinity. Despite the increase in the average EC value, the application of BAs did not alter the salinity class. The use of BAs also significantly influenced other analyzed parameters. An increase in the average content of total forms of Ca, Mg, K, and Na in the soil was observed, along with a higher degree of soil saturation with alkaline cations, compared to the control and the soil condition before the experiment. The changes in the analyzed soil parameters were significantly influenced not only by the different doses of BAs but also by the species of the cultivated plant. The greatest fluctuations in the obtained values were observed in soil under winter rape cultivation, while the smallest fluctuations were noted in soil under spring barley and potato cultivation.